Influence of Leadership on Job Satisfaction at Selected Government Organizations in Nairobi County - Isaac, Ochieng (2021)
Public organizations in Kenya have become vulnerable to losing their highly qualified, knowledgeable and experienced employees to well-paying public and private organizations. The consequences of losing such employees are dire since public organizations invest heavily on their employees in terms of recruitment, induction, training, development, maintaining and retaining of such employees. This study evaluated the influence of leadership on job satisfaction in selected government organizations in Nairobi County. To achieve this objective, the study was guided by Locke’s Value Theory, Maslow Hierarchy of Needs Theory and Herzberg Two Factor Theory. The study employed a descriptive research design. The population of this study was 5850 employees at both managerial and non-managerial positions in Teacher Service Commission, Kenya National Examination Council and Higher Education Loans Board. The sample size was 400 respondents. Data was collected using structured questionnaires. The collected data was analyzed using descriptive and inferential statistics. The response rate was 300 questionnaires representing 80.2% response rate.Findings established that leadershiphad a good correlation association with job satisfaction (r=0.642).The results indicated that there was a positive and significant association between leadership and job satisfaction. The study concluded that leadership is a critical element of enhancing job satisfaction among the employees of entities of the Ministry of Education. Thus, the leadership of these organizations should lead by example to inculcate employee job satisfaction. Keywords: Leadership, Job Satisfaction, Government organization, Nairobi County DOI: 10.7176/EJBM/13-12-06 Publication date:June 30th 202